2016
DOI: 10.1039/c5nj01788b
|View full text |Cite
|
Sign up to set email alerts
|

Size and shape trump charge in interactions of oxovanadates with self-assembled interfaces: application of continuous shape measure analysis to the decavanadate anion

Abstract: Using 51V NMR spectroscopy, dynamic light scattering and continuous shape analysis to characterize two polyoxometalate-encapsulation in reverse micelles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 166 publications
1
15
1
Order By: Relevance
“…The former (Figure S1) is consistent with previously reported results. 16 While the sharp feature at ∼1550 cm −1 is due to the ammonium counterion and the broad high-energy features are due to at least one O−H stretch (indicating protonation of one of the POM's exterior oxo ligands), the many overlapping features in the so-called "fingerprint region" cannot be assigned on the basis of this spectrum alone. Thus, we analyzed it alongside the rR spectrum in the 200−1200 cm −1 range (Figure 2).…”
contrasting
confidence: 61%
“…The former (Figure S1) is consistent with previously reported results. 16 While the sharp feature at ∼1550 cm −1 is due to the ammonium counterion and the broad high-energy features are due to at least one O−H stretch (indicating protonation of one of the POM's exterior oxo ligands), the many overlapping features in the so-called "fingerprint region" cannot be assigned on the basis of this spectrum alone. Thus, we analyzed it alongside the rR spectrum in the 200−1200 cm −1 range (Figure 2).…”
contrasting
confidence: 61%
“…The concentrations of each vanadate species V x were calculated from the fractions of the total integrated areas using the following equation: [V x ] = (A x /A t ) × ([V t ]/n), where A x corresponds to the area measured for the x vanadate species with n as the oligomer number (number of vanadium atoms), A t is the sum of the measured areas and [V t ] is the total vanadate concentration [71]. In the case of the decameric species, three signals at −420, −494 and −510 ppm were integrated for 2, 4 and 4 vanadium atoms, respectively [72].…”
Section: Kinetic Studiesmentioning
confidence: 99%
“…This size allowed for a V 10 molecule and a layer of 2–3 water molecules inside the water droplet. We also showed that a V 10 with a Mo [ 51 ] replacing one of the V-atoms, V 9 Mo, with similar shape but at a different charge behave similarly to V 10 [ 50 , 51 ]. These compounds are placed in the center of the water pool, however, we found that cations could change the system significantly [ 52 ].…”
Section: Resultsmentioning
confidence: 87%